EFFECT OF FEEDING CORN DRIED DISTILLERS GRAINS WITH SOLUBLES (DDGS) ON MILK PRODUCTION OF COW UNDER HOT CLIMATE CONDITION - Budi Tangendjaja (Indonesian Agency for Agricultural Research and Development, 2013)
Dried distillers grains with solubles (DDGS) is a co-product of ethanol industry made from grains through fermentation process and it can be used for animal feeding especially for dairy cows. A feeding trial on US corn DDGS was conducted at commercial dairy farm in Vietnam during hot condition in 2010. One hundred and fifty six dairy cows in a later stage of milk production were allotted randomly in three groups of 52 cows with similar milk production. Three dietary treatments offered comprised control diet, diet with 7.5% DDGS and diet with 15% DDGS. The diets were formulated to contain similar nutrient profiles and comprised forages (corn, elephant grass and alfalfa hay), brewery waste, soybean curd waste, corn, soybean meal, molasses and commercial dairy supplement. The diet was manufactured locally in total mixed ration system and delivered two times per day. Milk production, feed consump-tion and milk quality were measured for 5 days before the trial and 45 days after the trial. The result demonstrated that feeding DDGS could support higher milk production without affecting feed consumption. Feeding DDGS at 7.5% and 15% resulted in higher milk production of 2 and 4 kg per day respectively compared to cows fed control diet. Feed intake remained unaffected at around 35 kg per day. Milk quality as measured by total solid and fat content was similar in cows fed the control diet and DDGS at 7.5%. Feeding DDGS at 15% tended to have slightly better total solid and fat content. Feeding DDGS was able to reduce cost of the diets; diet cost for control, DDGS 7.5% and DDGS 15% were VND 2537, 2460 and 2399 per kg, respectively. It is concluded that DDGS can be economically used for feeding dairy cows in hot climate condition and improving milk production.